Protein leucine content is a determinant of shorter- and longer-term muscle protein synthetic responses at rest and following resistance exercise in healthy older women: a randomized, controlled trial. Issue 2 (26th February 2018) - Devries, Michaela C; McGlory, Christopher; Bolster, Douglas R; Kamil, Alison; Rahn, Maike; Harkness, Laura; Baker, Steven K; Phillips, Stuart M
ABSTRACT: Background: Older women may not be consuming enough protein to maintain muscle mass. Augmentation of protein intake with leucine may enhance the muscle protein synthetic response in older women to aid in maintaining muscle mass. Objective: We measured the acute (hourly) and integrated (daily) myofibrillar protein synthesis (myoPS) response to consumption of a high-quality mixed protein beverage compared with an isonitrogenous protein beverage with added leucine. Design: In a parallel design, free-living, healthy older women (aged 65–75 y, n = 11/group) consumed a fixed, weight-maintaining diet with protein at 1.0 g · kg –1 · d –1 and were randomly assigned to twice-daily consumption of either 15 g milk protein beverage containing 4.2 g leucine (LEU) or 15 g mixed protein (milk and soy) beverage containing 1.3 g leucine (CON). Unilateral leg resistance exercise allowed a determination of acute ([ 13 C6 ]-phenylalanine infusion, hourly rate) and integrated (deuterated water ingestion, daily rate) exercised and rested myoPS responses. Results: Acute myoPS increased in response to feeding in the rested (CON: 13% ± 4%; LEU: 53% ± 5%) and exercised (CON: 30% ± 4%; LEU: 87% ± 7%) leg in both groups, but the increase was greater in LEU ( P < 0.001). Integrated myoPS increased during the supplementation period in both legs (rested: 9% ±1%; exercised: 17% ± 2%; P < 0.001) in LEU, but in the exercised leg only (7% ± 2%; P < 0.001) in CON. Conclusions: A 15-g protein-containing beverage with ∼4 g leucine induced greater increases in acute and integrated myoPS than did an isonitrogenous, isoenergetic mixed-protein beverage. Declines in muscle mass in older women may be attenuated with habitual twice-daily consumption of a protein beverage providing 15 g protein and higher (4.2 g/serving) amounts of leucine. This trial was registered at clinicaltrials.gov as NCT02282566.